2017
DOI: 10.5194/bg-14-4533-2017
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture control of sap-flow response to biophysical factors in a desert-shrub species, <i>Artemisia ordosica</i>

Abstract: Abstract. The current understanding of acclimation processes in desert-shrub species to drought stress in dryland ecosystems is still incomplete. In this study, we measured sap flow in Artemisia ordosica and associated environmental variables throughout the growing seasons of 2013 and 2014 (May-September period of each year) to better understand the environmental controls on the temporal dynamics of sap flow. We found that the occurrence of drought in the dry year of 2013 during the leaf-expansion and leaf-exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 46 publications
6
27
0
1
Order By: Relevance
“…Plants in drylands generally experience more environmental stress, especially as severity and duration of droughts continue to increase under a warming climatic regime [7][8][9]. Consequently, it is expected that there will be changes in the supply of available plant resources, such as water (W), light (L), and nitrogen (N) for photosynthetic assimilation, as well as for the maintenance of functional plant structures.…”
Section: Introductionmentioning
confidence: 99%
“…Plants in drylands generally experience more environmental stress, especially as severity and duration of droughts continue to increase under a warming climatic regime [7][8][9]. Consequently, it is expected that there will be changes in the supply of available plant resources, such as water (W), light (L), and nitrogen (N) for photosynthetic assimilation, as well as for the maintenance of functional plant structures.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a close relationship between SWC and SF for a variety of tree species [16,19,40]. The results of regression analysis between SWC and SF are shown in Figure A1.…”
Section: Effect Of Meteorological Factors On Sfmentioning
confidence: 91%
“…In our study, we observed that the stem-scale SF differed notably with the SBD despite sharing the same diurnal variation ( Figure A4). Summarizing the different categories of plant morphological variables (Figure 6), the stem-scale SFs were significantly largest (p < 0.05) in the largest levels of PBN (18)(19)(20)(21)(22)(23)(24)(25), SL (230-270 cm), SBD (17-21 mm), and W (350-550 g), followed by those in the middle levels of PBN (11)(12)(13)(14)(15)(16)(17)(18), SL (190-230 cm), SBD (13-17 mm), and W (200-350 g), and lastly followed by those in the smallest levels of PBN (4-11), SL (150-190 cm), SBD (9-11 mm), and W (50-200 g). The regression analysis further indicated that the stem-scale SF of C. korshinskii had significantly positive linear correlations with PBN (Figure 7a), SL (Figure 7b), SBD (Figure 7c), and W ( Figure 7d)…”
Section: Effect Of Morphological Traits On Stem-scale Sfmentioning
confidence: 98%
See 2 more Smart Citations